Geoelectric hazard assessment: the differences of geoelectric responses during magnetic storms within common physiographic zones - Stephen W. Cuttler; Jeffrey J. Love; Andrei Swidinsky (Earth, Planets and Space, 2018)
Abstract Geomagnetic field data obtained through the INTERMAGNET program are convolved with with magnetotelluric surface impedance from four EarthScope USArray sites to estimate the geoelectric variations throughout the duration of a magnetic storm. A duration of time from June 22, 2016, to June 25, 2016, is considered which encompasses a magnetic storm of moderate size recorded at the Brandon, Manitoba and Fredericksburg, Virginia magnetic observatories over 3 days. Two impedance sites were chosen in each case which represent different responses while being within close geographic proximity and within the same physiographic zone. This study produces estimated time series of the geoelectric field throughout the duration of a magnetic storm, providing an understanding of how the geoelectric field differs across small geographic distances within the same physiographic zone. This study shows that the geoelectric response of two sites within 200 km of one another can differ by up to two orders of magnitude (4484 mV/km at one site and 41 mV/km at another site 125 km away). This study demonstrates that the application of uniform 1-dimensional conductivity models of the subsurface to wide geographic regions is insufficient to predict the geoelectric hazard at a given site. This necessitates that an evaluation of the 3-dimensional conductivity distribution at a given location is necessary to produce a reliable estimation of how the geoelectric field evolves over the course of a magnetic storm.